The Influence Of Motivation and Self Efficacy On Students' Interest In Careers In Taxation With Voluntability As Moderation - Kastanya, Mensy Otelyo; Ilham, Mohammad; Ipijei , Irene; Romdioni , Agus Nisfur (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This study aims to examine the effect of motivation and self-efficacy on student interest in a career in taxation with volunteerism as a moderating variable. The sampling technique in this study used purposive sampling, the samples obtained in this study were 50 students according to the criteria, namely students who took a tax concentration in the accounting department of the Faculty of Economics and Business at Musamus University. Data analysis technique uses Partial Least Square (PLS). The results showed that motivation had a positive effect on student interest in taxation (X1), Self Efficacy had a positive effect on student interest in taxation (X2), Volunteering did not moderate self-efficacy on student interest in taxation.